Rapid evolution of elaborate male coloration is driven by visual system in Australian fairy-wrens (Maluridae) - Friedman, N R; Remeš, V (Journal of evolutionary biology, 2015)
The interplay between colour vision and animal signalling is of keen interest to behavioural ecologists and evolutionary biologists alike, but is difficult to address in terrestrial animals. Unlike most avian lineages, in which colour vision is relatively invariant among species, the fairy-wrens and allies (Maluridae) show a recent gain of ultraviolet sensitivity (UVS). Here, we compare the rates of colour evolution on 11 patches for males and females across Maluridae in the context of their visual system. We measured reflectance spectra for 24 species, estimating five vision-independent colour metrics as well as metrics of colour contrast among patches and sexual dichromatism in a receiver-neutral colour space. We fit Brownian motion (BM) and Ornstein-Uhlenbeck (OU) models to estimate evolutionary rates for these metrics and to test whether male coloration, female coloration or dichromatism was driven by selective regimes defined by visual system or geography. We found that in general male coloration evolved rapidly in comparison with females. Male colour contrast was strongly correlated with visual system and expanded greatly in UVS lineages, whereas female coloration was weakly associated with geography (Australia vs. Papua New Guinea). These results suggest that dichromatism has evolved in Maluridae as males and females evolve at different rates, and are driven by different selection pressures.
Keywords: Animals; zrak; Female; biologická evoluce; Songbirds; barva; plumage coloration; ženské pohlaví; sexual dichromatism; zpěvní ptáci; Color; Phylogeny; Sex Factors; Male; sexuální faktory; colour vision; mužské pohlaví; zvířata; Biological Evolution; fylogeneze; Vision, Ocular; evolutionary rate